2022
DOI: 10.30880/ijscet.2022.13.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Plastic Waste as Eco-Friendly Aggregate for Sustainable Construction

Abstract: The advent of the COVID-19 pandemic has increased the amount of plastic waste. The demand for food and plastic-packaged foodstuffs has increased, and the use of disposable utensils has increased. The large usage of plastic packaging was the main factor which contributed to the plastic waste disposal. Since these plastic wastes are not easily degraded, it has led into massive environmental pollution. Transitioning towards eco-friendly materials fornewsustainabletechnologieswillbecriticaltocombatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Miftahorrozi et al (2022) menjelaskan bahwa Bank Sampah diartikan sebagai suatu mekanisme pengelolaan sampah kering secara kolektif yang mengajak serta masyarakat untuk aktif berpartisipasi. Melalui sistem ini, sampah yang dikumpulkan akan dikelola dengan cara dipilah-pilah, dan kemudian disalurkan ke pasar untuk mendapatkan nilai ekonomis (Adiyanto et al, 2022). Masyarakat tidak hanya berkontribusi dalam pengurangan volume sampah, tetapi juga mendapatkan keuntungan finansial dari praktik pengelolaan sampah yang berkelanjutan (Adiyanto et al, 2023;Ismiraj et al, 2023).…”
Section: Pendahuluanunclassified
“…Miftahorrozi et al (2022) menjelaskan bahwa Bank Sampah diartikan sebagai suatu mekanisme pengelolaan sampah kering secara kolektif yang mengajak serta masyarakat untuk aktif berpartisipasi. Melalui sistem ini, sampah yang dikumpulkan akan dikelola dengan cara dipilah-pilah, dan kemudian disalurkan ke pasar untuk mendapatkan nilai ekonomis (Adiyanto et al, 2022). Masyarakat tidak hanya berkontribusi dalam pengurangan volume sampah, tetapi juga mendapatkan keuntungan finansial dari praktik pengelolaan sampah yang berkelanjutan (Adiyanto et al, 2023;Ismiraj et al, 2023).…”
Section: Pendahuluanunclassified
“…It is observed that compressive strength increases with an increase in plastic content, while a decrement in hardness is recorded by the R-scale Rockwell hardness number test (HRR). Adiyanto et al [120] introduced 1.65 kg and 2.38 kg of plastic waste with the addition of cement, sand, and quarry dust. It is observed that compressive strength increases with an increase in plastic content by the 7 th , 14 th , and 21 st days of observation.…”
Section: Mouldablementioning
confidence: 99%
“…5 Besides, plastics are also made of chemical polymers that cannot be degraded naturally so that plastic will not decompose even if buried. 6 Combinations of synthetic polymers such as polyethylene, polyamide, polypropylene, polystyrene, polyethylene terephthalate, and polyvinyl chloride are often used as packaging materials. 7 Polymer waste such as post-consumption plastic is the main component of solid waste that creates a very large environmental burden because it is not easily degraded.…”
Section: Introductionmentioning
confidence: 99%
“…Those contemplate the reasons why eco-bricks might be utilized as a choice for building construction materials. 6,[21][22][23] Furthermore, the reuse of PET plastic bottles as building materials will have a good effect on energy savings and also will reduce CO2 emissions. 20 The performance of eco-brick as a construction alternative depends on the material used and the power to fill the bottle.…”
Section: Introductionmentioning
confidence: 99%